Identifikasi Intensitas Aktivitas Kerja Awak Kapal Purse seine di Perairan Selat Malaka - Suci Asrina Ikhsan; Sri Yenica Roza; Ratih Purnama Sari; Roma Yuli F. Hutapea; Muhammad Zaki Latif Abrori (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2022)
Work intensity measures how much to do an activity that uses a measurement scale. The intensity of work in doing a lot of work causes the crew to become tired, reduces performance and concentration, and affects the crew's safety. Fatigue and reduced concentration at work have the potential to cause work accidents. The work intensity of the crew on the operation of purse seine fishing gear is influenced by the stages of work activity. The stages of this activity consist of primary and secondary activities. The purpose of this research is to find out the work intensity of crew activities on the operation of purse seine fishing gear in the waters of the Malacca Strait (WPP 571). The method used is hierarchical task analysis. The high intensity of work on purse seine vessels is when carrying out fishing operations. The fishing is in the 5th stage, namely hauling or lifting the net. Using purse seine gear, work on fishing vessels has 56 primary and seven secondary activities. The total work intensity (IKT) on the purse seine operation is 2501 OA (activity person), the high work intensity and rest time on the purse seine ship still meet the STCW Manila amendment.